E-LEARNING IMPLEMENTATION: ITS OPPORTUNITIES AND DRAWBACKS PERCEIVED BY EFL STUDENTS - Rahmawati, Fitria (Journal of Foreign Language Teaching and Learning, 2016)
Technology provides numerous assistances for education, particularly for language learning. By the presence of technology, students get exposures to Internet which enables them to interact and communicate with native speakers, the experience of which may not be available for in-class activi- ties in general. In other words, students are given chances to be exposed to a more interesting and interactive learning instruction. The implementation of e-learning, thus, becomes one alternative to teaching techniques which empowers students to be more active language users. This study high- lights the integration of e-learning into language teaching and learning. It aims to investigate students? perceptions on what opportunities and drawbacks e-learning brings to their language learning. This study involved a private university which offered some courses implementing e- learning. During the courses, the students were required to participate in e-learning inside and outside the classroom. The activities included commenting on a thread, analysing a specific topic or case, submitting assignments, responding to other students? comment or work, taking polls, doing quizzes, and accomplishing a project. The findings from interviewing the six participants revealed some issues related to how they perceived the opportunities that e-learning provided and also the drawbacks that e-learning created.